2022
DOI: 10.3233/jad-215198
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Psychological Symptoms of Dementia in Different Dementia Disorders: A Large-Scale Study of 10,000 Individuals

Abstract: Background: The majority of individuals with dementia will suffer from behavioral and psychological symptoms of dementia (BPSD). These symptoms contribute to functional impairment and caregiver burden. Objective: To characterize BPSD in Alzheimer’s disease (AD), vascular dementia (VaD), mixed (Mixed) dementia, Parkinson’s disease dementia (PDD), dementia with Lewy bodies (DLB), frontotemporal dementia (FTD), and unspecified dementia in individuals residing in long-term care facilities. Methods: We included 10,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 53 publications
3
39
0
Order By: Relevance
“…A Swedish registry study on cognitive disorders and dementia revealed that individuals with VaD had a higher risk of apathy, but a lower risk of agitation or aggression, anxiety, and aberrant motor behavior. Agitation and aggression are more relevant to mixed-type dementia than to VaD [ 86 ]. A study conducted at three major medical centers in Taiwan enrolled 97 patients with BPSD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Swedish registry study on cognitive disorders and dementia revealed that individuals with VaD had a higher risk of apathy, but a lower risk of agitation or aggression, anxiety, and aberrant motor behavior. Agitation and aggression are more relevant to mixed-type dementia than to VaD [ 86 ]. A study conducted at three major medical centers in Taiwan enrolled 97 patients with BPSD.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium benzoate treatment improved cognitive function (in terms of ADAS-cog scores) only in women with later-phase dementia (15). Sodium benzoate exerted antipsychotic properties in patients with schizophrenia [ 86 ]. However, it did not mitigate psychotic symptoms in patients with dementia.…”
Section: Resultsmentioning
confidence: 99%
“…Although dementia is defined largely by memory and cognitive decline which results in the loss of the ability to function independently, behavioral and psychological symptoms in dementia (BPSD) play a large role in a patient's overall functional level [1]. Significant BPSD are more the rule than the exception, as >90% of people with dementia develop BPSD during the disease course [2,3]. BPSD encompass a wide array of symptoms and include aggression, agitation, hyperactivity, compulsions, disinhibition, anxiety, depression and dysphoria, euphoria delusions, and hallucinations.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, it has been found that a surprising number of individuals living with dementia do not receive any post-diagnosis support beyond the information they received at diagnosis (2). Indeed, in addition to the symptom of cognitive decline, individuals with dementia frequently manifest behavioral and psychological disturbances like agitation, depression, anxiety, apathy, and delusions, among others (3)(4)(5). It is estimated that 80-90% of patients with dementia develop behavioral and psychological symptoms of dementia (BPSD) during their illness (6).…”
Section: Introduction Rationalementioning
confidence: 99%